The First Record of Metaphire Birmanica (Rosa, 1888) in Vietnam, with Notes on Several Earthworm Species - Lam, Dang Hai; Nguyen, Anh Duc; Nguyen, Tung Thanh (Jurnal Biodjati, 2020)
The Amynthas and Metaphire species recorded in Vietnam have been rechecked based on original descriptions and preserved specimens. As a result, Metaphire birmanica (Rosa, 1888) is recorded in Vietnam for the first time. The species is recognized by having three pairs of spermathecal pores in 5/6/7/8, male pores in xviii, presence of copulatory pouches, no genial markings, and manicate intestinal caeca. In addition, three species have been rechecked and re-assigned to different genera, namely Amynthas tripidoporophoratus (Thai & Nguyen, 1993) comb. nov., Metaphire dranfocana (Do & Huynh, 1993) comb. nov., Metaphire anhumalatana (Thai & Huynh, 1993) comb. nov.